Dummy Text, or The Diagrammatic Basis of Contemporary Architecture - D'Angelis, Camilo Kolomi Veiga (Risco - Journal of Architecture and Urbanism, 2021)
Translation into Portuguese of Dummy Text, by Robert Somol, opening text of the book Diagram Diaries (1999), by Peter Eisenman, which explores the context of theoretical production and the architect's work over the nearly 40 years that separate the presentation of his doctoral thesis in philosophy (Trinity College, University of Cambridge, 1963) from the publication of the book.